The Government and the News-Print Paper Manufacturers - Merchant, E. O. (Quarterly Journal of Economics, 1918)
Introduction, 238. — I. The Federal Trade Commission's investigation; its arbitration, 239. — The industry from 1910 to 1915, 240. — Rise in prices in 1916, 241. — Situation of the publishers, 243. — Arbitration by the Commission, 244. — Action of Department of Justice, 244. — Arbitration agreement falls through, 246. — II. Proceedings by the Department of Justice, 248. — Agreement for settlement of prices by Trade Commission, 249. — Injunction dissolving the Manufacturers' Association, 250. — III. Other developments, 251. — Recommendations to Congress for government control during the war, 251. — The Smith bill, 252. — Continuous cost reports, 252. — Statistical service instituted, 253. — Conclusion, 254.